Effect of gymnastics elderly on the changes of osteoarthritis pain - Widodo, Heriadi; Redjeki, Dwi Sogi Sri; Mahdiyah, Dede; Irawan, Angga; Al Kahfi, Rina (Ananda - Health & Education Foundation, 2024)
Background: Osteoarthritis is a chronic joint disorder where there is a process of attenuation and disintegration of joint cartilage accompanied by bone growth and new cartilage in the joints. Patients with osteoarthritis occur at the age of 40-60 years; one of the roles of nurses in improving the quality of life of the elderly is to overcome health problems that commonly occur in the elderly. One of them is joint pain management due to osteoarthritis by using non-pharmacological therapy in the form of elderly exercises. Objective: Identify the influence of elderly gymnastics on changes in osteoarthritis pain in social institutions Tresna Werdha Budi Sejahtera Banjarbaru. Method: This study uses a quantitative method with experimental quasi with the research design used is a pretest-posttest one group design. Initial data collection before and after intervention. Results: Respondents who experienced knee ostearthritis pain before elderly exercise can be seen that most respondents have characteristics of moderate pain. The biggest complaint presentation was experiencing moderate pain, which was 30 people (100%) on the first day. Wilcoxon test results found the quality of knee osteoarthritis pain in the elderly before and after a significant compress. This is based on the p-value of 0.000, which means that there is an influence of elderly gymnastics on the reduction in the quality of knee osteoarthritis pain in the elderly in social care institutions because there is prosperity in Banjarbaru. Conclusion: There is a relationship between the effect of elderly gymnastic therapy to reduce osteoarthritis of knee pain suffered by the elderly.